In situ post-ischemic conditioning by temporary balloon occlusion for acute ischemic stroke: a modified reperfusion technique and adverse event monitoring - Wang, Sifei; Liu, Shuai; Zhang, Bohao; Jiang, Xiao; Wei, Ming; Yan, Hua (Frontiers in Neurology, 2025)
BackgroundWith the development of endovascular therapy, the success rate of reperfusion for emergent large vessel occlusion (LVO) has significantly improved, but more achievements are still needed. In situ post-ischemic conditioning (IPC) is a modified reperfusion technique and a neuroprotective method. It is potentially promising for patients with acute ischemic stroke (AIS) and can improve the outcome; however, the IPC technique has not been well defined.MethodsThe definition and technical details of in situ post-ischemic conditioning using neurointerventional strategies were defined in this prospective cohort. Consecutive patients treated with the IPC technique between January 1, 2022, and Jun 30, 2023, were included in this study. Patients’ demographic and technical performance of the IPC procedure were recorded. Adverse events related to the IPC procedure were actively monitored and analyzed.ResultsIn total, 40 patients underwent IPC. Their mean age was 65 years (IQR, 34–83), and 72.5% were male. The median ASPECTS (Alberta Stroke Program Early CT Score) was 7. The median of NIHSS was 13. The preset IPC program was achieved in 95.0% of cases, with 0% procedure-related mortality and 2.5% morbidity. The incidence of procedure-related dissection was 0%. The incidence of thrombotic events was 2.5%. Extravasation of contrast media was recorded as a serious adverse event. One thrombotic event occurred in the LAA Group. However, there was no statistical difference in the incidence of adverse events between the LAA and non-LAA groups. The LAA and MCA groups had shorter IPC procedure times compared with non-LAA and ICA groups.ConclusionThe IPC technique is safe and feasible with an acceptable complication rate.